2021
DOI: 10.3389/fpsyg.2021.773363
|View full text |Cite
|
Sign up to set email alerts
|

Metric Goodness and Measurement Invariance of the Italian Brief Version of Interpersonal Reactivity Index: A Study With Young Adults

Abstract: The Interpersonal Reactivity Index (IRI) is a widely used multidimensional measure to assess empathy across four main dimensions: perspective taking (PT) empathic concern (EC) personal distress (PD) fantasy (F). This study aimed to replicate the Italian validation process of the shortened IRI (Interpersonal Reactivity Index) scale in order to confirm its psychometric properties with a sample of young adults. The Gender Measurement Invariance of empathy in this age group was also an objective of the work in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…Given the role that rumination is thought to play in the onset of teenage depression (98)(99)(100), it seems important to study the specificity of this cognitive vulnerability factor in this particular age group. Some scholars have pointed out that the presence of rumination is often related to increased anger, embarrassment, and negative affectivity (101)(102)(103).…”
Section: Discussionmentioning
confidence: 99%
“…Given the role that rumination is thought to play in the onset of teenage depression (98)(99)(100), it seems important to study the specificity of this cognitive vulnerability factor in this particular age group. Some scholars have pointed out that the presence of rumination is often related to increased anger, embarrassment, and negative affectivity (101)(102)(103).…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve this objective, the communication style adopted within the groups and the dynamics of interpersonal responsiveness are also relevant [96][97][98][99]. In the study by Ho and Holroyd [100], it was reported that women often identified that it was impossible to engage in questioning and discussion, to have their personal problems addressed, to make friends, and for the educators to seek appropriate feedback from their clients.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other countries ( 59 – 62 ), Italy does not currently have any specific awareness campaigns on the risk of hepatitis C for university students. Instead, more preventive actions should be promoted through programmes organized in the form of lectures, symposia, conferences, radio programmes, and health talks using all kinds of public platforms and social media, and also through appropriate communication styles that can foster greater interpersonal responsiveness and empathic involvement ( 63 67 ). Several studies show that health promotion actions in university settings through active involvement methodologies can produce significant effects in terms of prevention and behavioral change ( 68 73 ).…”
Section: Discussionmentioning
confidence: 99%